Longer-Term Impact of the Flavored Tobacco Restriction in Two Massachusetts Communities: A Mixed-Methods Study. Issue 11 (9th June 2021) - Kingsley, Melody; Setodji, Claude M; Pane, Joseph D; Shadel, William G; Song, Glory; Robertson, Jennifer; Kephart, Lindsay; Zepeda, Samantha; Henley, Patricia; Ursprung, W W Sanouri
Abstract: Introduction: In response to high rates of youth tobacco use, many states and localities are considering regulations on flavored tobacco products. The purpose of this study was to assess whether flavored tobacco restrictions (FTRs) in Massachusetts curb youth tobacco use over time and whether a dose–response effect of length of policy implementation on tobacco-related outcomes exists. Aims and Methods: Using a quasiexperimental design, two municipalities with a FTR (adopting municipalities) were matched to a comparison municipality without a FTR. Surveys were administered before (December 2015) and after (January and February 2018) policy implementation to high school students in these municipalities (more than 2000 surveys completed at both timepoints). At follow-up, adopting municipalities had a policy in place for 1 and 2 years, respectively. In 2019, focus groups were conducted with high school students in each municipality. Results: Increases seen in current tobacco use from baseline to follow-up were significantly smaller in adopting municipalities compared to the comparison (−9.4% [−14.2%, −4.6%] and −6.3% [−10.8%, −1.8%], respectively). However, policy impact was greater in one adopting municipality despite shorter length of implementation. Focus groups indicated reasons for differential impact, including proximity to localities without FTRs. Conclusions: Restrictions implemented in adopting municipalities had positive impacts on youth tobacco awareness and use 1–2 years postimplementation. Policy impact varies depending on remaining points of access to flavored tobacco, as such policy effectiveness may increase as more localities restrict these products. Implications: In response to high rates of youth flavored tobacco use (including flavored vape products), federal, state, and localities have passed FTRs that reduce availability of flavored tobacco in youth-accessible stores. Previous research has found that FTRs may curb youth tobacco use in the short-term; however, the long-term effectiveness remains unknown. This is the first study to show FTRs can curb youth tobacco use and reduce youth awareness of tobacco prices and brands even 2 years after policy passage. Municipality-specific factors, including proximity to localities without FTRs, may attenuate policy impact, highlighting the importance of widespread policy adoption.